Granitic pegmatites in Sri Lanka: A concise review leading to insights and predictions. (March 2021) - Dharmapriya, P.L.; Disanayaka, D.W.M.; Martin, Robert F.; Pitawala, H.M.T.G.A.; Malaviarachchi, Sanjeewa P.K.
Abstract: Granitic pegmatites can be a source of frustration and confusion. It is thus appropriate to begin with a quick review of basic concepts. Crystallization takes place in the presence of two fluid media; one is a viscous, polymerized silicate magma, and the other is a supercritical aqueous fluid. The two are largely but not completely immiscible. The proportion of aqueous fluid in the mixture progressively increases as the amount of melt diminishes. Pegmatites are of significant economic interest, as they are source rocks of industrial minerals like quartz and the feldspars. These minerals crystallized from the magma, but the feldspars generally become modified by the aqueous fluid. The same applies to accessory minerals that carry Nb, Ta, Zr, Sn and the rare earths. At a late stage, the magmatic fluid phase mixes with cooler, externally derived fluids that bring in elements like Ca and Mg, present in the latest generation of cavity minerals. Frustration arises because the question is recurrent concerning what is magmatic and what is post-magmatic. In terms of tectonic setting, granitic pegmatites may occur in contexts of crustal compression or crustal extension. The pegmatites of Sri Lanka, some of them syenitic and found in all four lithotectonic domains on the island, seem to be unrelated to central plutons. Rather, they are of anatectic origin and members of the NYF family. Some are deformed, but the largest ones are not. Mineralogical and geochemical indicators point to crystallization of the magmas largely in an environment of tectonic relaxation, as in the Grenville collision zone. Important questions remain about the timing of pegmatite emplacement, the interplay of anorogenic magmatism at the end of the Pan-African orogeny, and the role of the mantle in providing heat and fluids that led to localized anatexis of the granulite-grade metamorphic rocks .